Criticalidade da carga central na termodinâmica de buracos negros anti-de sitter cercados por diferentes fluidos - Alfaia, Ramon Baia de (2022)
This dissertation is inserted in the general context of Black Hole Thermodynamics. After introducing the fundamentals of the General Theory of Relativity, we consider the specific purpose of the work: the investigation of the Laws of Black Hole Thermodynamics in the context of Kiselev’s geometry in D dimensions in the presence of different kinds of fluids. We present the laws of thermodynamics for the model and analyze the critical behavior of the model in the holographic approach recently proposed in (CONG; KUBIZNAK; MANN, 2021). As a result, we show that the holographic technique remains valid for Kiselev geometry when the extended phase space is generalized to incorporate a thermodynamics with a variable gravitational constant.